2023
DOI: 10.1002/jcop.23009
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of resilience in the relationship between helicopter parenting and several indicators of mental health among emerging adults

Abstract: Helicopter parenting has received much attention in the last decade. The growing literature on this phenomenon illustrates the negative consequences of helicopter parenting. The detrimental effects of helicopter parenting on emerging adults may be especially more present in collectivist cultures. Studies carried out with this population have demonstrated that mental health problems among this group are more prevalent than those of other groups. Hence, an understanding of the factors affecting mental health at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…In our study, we nevertheless found low helicopter parenting levels. Moreover, the resilience found in our sample might have decreased the likelihood of exhibiting depression, anxiety, and stress symptoms even in the case of overprotective parenting, in line with the literature [ 67 ]. Our study showed that trainees’ resilience was higher when they received more support at the workplace.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we nevertheless found low helicopter parenting levels. Moreover, the resilience found in our sample might have decreased the likelihood of exhibiting depression, anxiety, and stress symptoms even in the case of overprotective parenting, in line with the literature [ 67 ]. Our study showed that trainees’ resilience was higher when they received more support at the workplace.…”
Section: Discussionsupporting
confidence: 90%
“…Our study showed low mean scores of helicopter parenting style among our sample, and a lack of association with the medical trainees’ mental health outcomes. This might be related to cultural context, however, literature shows larger detrimental effects of helicopter parenting in collectivist cultures than in individualistic cultures [ 66 , 67 ]. In collectivist cultures, like the context of our study, university students do not work and depend on their parents financially during their university education.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of changes in work, life, and learning styles, parents and their children have experienced extraordinary pressure. Several studies have demonstrated that helicopter parenting in such extreme circumstances may have more adverse consequences on children's mental health and conduct, potentially impairing their ability to develop the psychological resilience needed to cope with adversity [70][71][72]. In the foregoing context, this study found that helicopter parenting leads to significant negative consequences for college students.…”
Section: Conclusion and Discussionmentioning
confidence: 60%
“…These parents, who try to control their children's environment, unintentionally prevent their children from encountering new experiences and learning about the world (Awiszus et al, 2021). Discussions continue about these parents who use an unhealthy coping strategy for today's threat conditions their children face (Seki et al, 2023). On the other hand, Lee et al (2014) indicate both advantages and disadvantages of helicopter parenting.…”
Section: Learning Is Enhanced By Challenge and Inhibited By Threatmentioning
confidence: 99%